User satisfaction: Measurement and interpretation. Issue 1 (1st January 2001) - Harris, Janet; Westerby, Martin; Hill, Tony; Sellers, Tilly; Hutchinson, Anne
Abstract : Over the past 5 years there has been an increased interest in assessing users' satisfaction with health care services in England. Measuring and interpreting user satisfaction with reproductive and sexual health services can be complex, and efforts have met with varying degrees of success. This paper will summarise the methods that have been used to assess user satisfaction over the past 10 years, describe a different type of approach that has been recently used in England, and provide some suggestions for approaches that may be effective in improving clinical effectiveness in the new millennium.